Metal monatomic / polydopamine / cadmium sulfide composite material as well as preparation method and application thereof
By using metal single atom/polydopamine/cadmium sulfide composite materials as photocatalysts, the problem of difficulty in regulating the selectivity of the photocatalyst during the oxygen reduction process and serious electron and hole recombination is solved, and an efficient hydrogen peroxide yield is achieved, and a green synthesis method is provided.
Patent Information
- Application Number
- CN202411727740.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
AI Technical Summary
During the oxygen reduction process, existing photocatalysts have problems such as difficulty in controlling selectivity, serious electron and hole recombination, resulting in low hydrogen peroxide yield, insufficient supply of protons and electrons, and unclear structure of reactive sites.
The metal single atom/polydopamine/cadmium sulfide composite material is used as the photocatalyst, and the cadmium sulfide nanoparticles are wrapped by polydopamine and supported by metal single atoms, and the composite material is formed by using photodeposition reaction to achieve efficient reduction of oxygen to hydrogen peroxide.
Under visible light excitation, composite materials can effectively separate electrons and holes, improve the yield of hydrogen peroxide, and achieve high yields under mild reaction conditions, reducing costs and providing a green synthesis method.
Smart Images

Figure CN119549196A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocatalysts, and in particular to a metal single atom / polydopamine / cadmium sulfide composite material and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Hydrogen peroxide (H2O2) is considered to be a clean energy that is expected to replace hydrogen energy. It can be used for battery power generation, and the energy density of its aqueous solution is comparable to that of compressed hydrogen. It is safer to store and transport than compressed hydrogen. In addition, hydrogen peroxide, as an efficient and green oxidant, is widely used in the chemical industry and environmental remediation, such as pulp and paper bleaching, electronics industry, disinfection and water treatment.
[0004] At present, the commercial production of hydrogen peroxide mostly adopts the anthraquinone method. Although it is efficient, the anthraquinone method for producing hydrogen peroxide is costly, the process is complicated, and there are a lot of toxic byproducts. These shortcomings limit the widespread application of this method. Although electrocatalytic redox and precious metal catalytic reactions of hydrogen and oxygen do not produce toxic byproducts in the process of synthesizing hydrogen peroxide, these two methods have high energy consumption and may be explosive. Therefore, it is urgent to develop a simple and safe method for synthesizing hydrogen peroxide.
[0005] Artificial photosynthesis can convert solar energy into chemical energy through photochemical reactions. Driven by solar energy, the photogenerated electrons produced by photocatalysts reduce oxygen to form superoxide radicals; the generated holes oxidize water to form hydrogen ions and oxygen, where hydrogen ions combine with superoxide radicals to form hydrogen peroxide. Compared with traditional methods, photocatalytic synthesis of hydrogen peroxide has the advantages of low energy consumption and environmental friendliness. However, the photocatalysts reported so far still have the following problems: for example, water is easily generated during the oxygen reduction process, and there is a problem of difficulty in regulating selectivity; the photocatalyst has serious electron and hole recombination during the reaction, resulting in a low hydrogen peroxide yield; a large number of protons and electrons are required during the oxygen reduction process, and there is a problem of insufficient proton and electron supply; the structural evolution of the reaction active site for the generation of hydrogen peroxide is unclear, and the reaction mechanism for the generation of hydrogen peroxide is unclear. Summary of the invention
[0006] In order to overcome the above problems, the present invention provides a metal single atom / polydopamine / cadmium sulfide composite material and a preparation method and application thereof.
[0007] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0008] The first aspect of the present invention provides a metal single atom / polydopamine / cadmium sulfide composite material, which is based on polydopamine-wrapped cadmium sulfide nanoparticles and loaded with metal single atoms.
[0009] The second aspect of the present invention provides a method for preparing the metal single atom / polydopamine / cadmium sulfide composite material according to the first aspect, comprising the following steps:
[0010] (1) dispersing cadmium sulfide nanoparticles in an alkaline buffer solution, adding dopamine hydrochloride, and reacting to obtain polydopamine-coated cadmium sulfide nanoparticles;
[0011] (2) Mixing a metal single atom source with polydopamine-wrapped cadmium sulfide nanoparticles to obtain a mixture; the mixture undergoes a photodeposition reaction to obtain the metal single atom / polydopamine / cadmium sulfide composite material.
[0012] The third aspect of the present invention provides the use of the metal single atom / polydopamine / cadmium sulfide composite material described in the first aspect and / or the metal single atom / polydopamine / cadmium sulfide composite material prepared by the preparation method described in the second aspect as a photocatalyst.
[0013] A fourth aspect of the present invention provides a method for synthesizing hydrogen peroxide, comprising: adding the metal single atom / polydopamine / cadmium sulfide composite material described in the first aspect and / or the metal single atom / polydopamine / cadmium sulfide composite material prepared by the preparation method described in the second aspect to water, introducing oxygen and reacting under a light source to obtain hydrogen peroxide.
[0014] The beneficial effects of the present invention are:
[0015] (1) Under visible light excitation, the metal single atom / polydopamine / cadmium sulfide composite material generates electron-hole pairs and separates, where the holes are distributed in the valence band of CdS (VB) and the electrons are distributed in the conduction band of CdS (CB). The electrons distributed in the conduction band of CdS are transferred to the surface of the metal single atom through polydopamine. Finally, the photogenerated electrons are distributed on the metal single atom and the photogenerated holes are distributed in the valence band of CdS. When the reaction occurs, oxygen is first oxidized by the metal single atom to superoxide ions (·O2 - ), water is reduced to H by the holes in the CdS valence band. + , polydopamine will H + Transferred to the metal surface, O2 - and photogenerated electrons and H + Combined with H + Combine to form H2O2.
[0016] (2) The present invention uses abundant and cheap water as the hydrogen source and oxygen as the raw material, and does not add expensive sacrificial agents, etc., which greatly reduces the cost and provides a new green method for the preparation of hydrogen peroxide.
[0017] (3) The present invention utilizes a metal single atom / polydopamine / cadmium sulfide composite material as a multiphase photocatalyst. The reaction conditions are mild and a very high hydrogen peroxide yield can be obtained at room temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0019] Figure 1 0.01wt%Mn SAC / SEM images of PDA-CdS NRs;
[0020] Figure 2 0.01wt%Mn SAC / PDA-CdS NRs transmission electron microscopy image;
[0021] Figure 3 0.01wt%Mn SAC / Contact angle test diagram of PDA-CdS NRs;
[0022] Figure 4 0.01wt%Mn SAC Infrared spectrum of / PDA-CdS NRs. DETAILED DESCRIPTION
[0023] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0024] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0025] A first typical embodiment of the present invention provides a metal single atom / polydopamine / cadmium sulfide composite material, which is based on cadmium sulfide nanoparticles wrapped with polydopamine and loaded with metal single atoms.
[0026] In one or more embodiments, the metal single atom is selected from single-atom Cu, single-atom Co, single-atom Zn, single-atom Fe, single-atom Ni, single-atom Nb, single-atom In, single-atom Pr, single-atom La, single-atom Eu, single-atom V, single-atom Mo, single-atom Mn, single-atom Cr, single-atom W, single-atom Zr, single-atom Si, single-atom Al, single-atom Mg, single-atom Re, single-atom Ru, single-atom Re, single-atom Au, single-atom Pt, single-atom Pd and single-atom Ir, preferably one of single-atom Co, single-atom Fe, single-atom Ni and single-atom Mn, and further preferably single-atom Mn.
[0027] In one or more embodiments, in the metal single atom / polydopamine / cadmium sulfide composite material, the metal single atom loading is 0.005 wt% to 1 wt%, preferably 0.01 wt% to 0.2 wt%.
[0028] In one or more embodiments, the cadmium sulfide nanoparticles are cadmium sulfide nanorods or cadmium sulfide nanospheres; preferably, the cadmium sulfide nanorods are about 2 to 3 μm long and about 50 nm wide; and the cadmium sulfide nanospheres are about 250 to 300 nm.
[0029] A second typical embodiment of the present invention provides a method for preparing the metal single atom / polydopamine / cadmium sulfide composite material according to the first aspect, comprising the following steps:
[0030] (1) dispersing cadmium sulfide nanoparticles in an alkaline buffer solution, adding dopamine hydrochloride, and reacting to obtain polydopamine-coated cadmium sulfide nanoparticles;
[0031] (2) Mixing a metal single atom source with polydopamine-wrapped cadmium sulfide nanoparticles to obtain a mixture; the mixture undergoes a photodeposition reaction to obtain the metal single atom / polydopamine / cadmium sulfide composite material.
[0032] In one or more embodiments, in step (1), the mass ratio of cadmium sulfide nanoparticles to dopamine hydrochloride is (12-14):(1.5-2), preferably 12.75:1.88.
[0033] In one or more embodiments, in step (1), dopamine hydrochloride is added and stirred to react to obtain polydopamine-wrapped cadmium sulfide nanoparticles. The stirring rate is 200 to 300 rpm, preferably 220 rpm; and the stirring time is 2 to 8 hours.
[0034] In one or more embodiments, in step (1), the alkaline buffer solution is a Tris-HCl aqueous solution.
[0035] In one or more embodiments, in step (2), the metal single atom source includes CuCl2, ZnCl2, Fe(NO3)3, C 10 H5B 20 , InCl3, PrCl3, Cl3La, C6H9EuO6, Cl3V, C8H 12 Mo2O8, C6H9O6Cr, WCl6, C8H 12 O8Zr、C8H 12 One of O8Si, AlCl3, MgCl2, Cl5Re, C6H9O6Ru, HAuCl4, HPtCl4, PdCl2, Cl4Ir, Mn(CH3COO)2, Ni(CH3COO)2, CoSO4 and Fe(NO3)3.
[0036] In one or more embodiments, in step (2), a metal single atom source is mixed with cadmium sulfide nanoparticles wrapped with polydopamine to obtain a mixture; and the mixture undergoes a photodeposition reaction to obtain the metal single atom / polydopamine / cadmium sulfide composite material. The method comprises:
[0037] The method comprises dispersing a metal single atom source and cadmium sulfide nanoparticles wrapped by polydopamine in water, mixing them evenly, and then irradiating the mixed solution with a 200-400W xenon lamp for 15-30 minutes under a vacuum state to obtain the metal single atom / polydopamine / cadmium sulfide composite material.
[0038] Preferably, the mixed solution is irradiated with light for 20 minutes using a 300W xenon lamp in a vacuum state.
[0039] A third typical embodiment of the present invention provides the use of the metal single atom / polydopamine / cadmium sulfide composite material described in the first aspect and / or the metal single atom / polydopamine / cadmium sulfide composite material prepared by the preparation method described in the second aspect as a photocatalyst.
[0040] In one or more embodiments, the use includes photocatalytic synthesis of hydrogen peroxide from oxygen and water.
[0041] A fourth typical embodiment of the present invention provides a method for synthesizing hydrogen peroxide, comprising: adding the metal single atom / polydopamine / cadmium sulfide composite material described in the first aspect and / or the metal single atom / polydopamine / cadmium sulfide composite material prepared by the preparation method described in the second aspect to water, introducing oxygen and reacting under a light source to obtain hydrogen peroxide.
[0042] In one or more embodiments, the power of the light source is 30-90 W, and the wavelength of the light source is 300-600 nm.
[0043] In one or more embodiments, the temperature for the reaction under the light source is 25 to 90°C.
[0044] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0045] Example 1
[0046] Cadmium sulfide nanorods (CdS NRs) were synthesized by hydrothermal synthesis:
[0047] Dissolve 4.62g of cadmium chloride (pentahydrate) and 4.62g of thiourea in 60mL of ethylenediamine and stir for 60min. Transfer the mixed solution to a 100mL polytetrafluoroethylene reactor and hydroheat at 180℃ for 24h. Cool the reactor to room temperature, wash the cadmium sulfide material with ethanol three times, and dry it in an oven at room temperature for 24h.
[0048] The size of cadmium sulfide nanorods is about 2 to 3 μm in length and about 50 nm in width.
[0049] Example 2
[0050] Cadmium sulfide nanospheres (CdS NPs) were synthesized by hydrothermal synthesis:
[0051] Cd(Ac)2 (1.60 g, 6.94 mmol) and thiourea (1.40 g, 18.39 mmol) were dissolved in 0.12 L of deionized water. The solution was transferred to a 100 mL polytetrafluoroethylene reactor and kept at 180 °C for 12 hours. After centrifugation and washing with water and ethanol for 4 times, it was dried at 80 °C for 12 hours.
[0052] The size of cadmium sulfide nanospheres is 250-300 nm.
[0053] Example 3
[0054] Preparation of polydopamine-coated cadmium sulfide nanorods (PDA-CdS NRs):
[0055] 127.5 mg of CdS NRs synthesized in Example 1 were dispersed in 50 mL of Tris-HCl aqueous solution (1 M, 2.5 mL, pH = 8.8) and 47.5 mL of water, followed by the addition of 18.8 mg of dopamine hydrochloride. The reaction suspension was then stirred at 30°C and 220 rpm for 2 h. The mixture was centrifuged, washed with water and ethanol three times, and dried at 60°C, labeled as PDA-CdS-2h NRs.
[0056] 127.5 mg of CdS NRs synthesized in Example 1 were dispersed in 50 mL of Tris-HCl aqueous solution (1 M, 2.5 mL, pH = 8.8) and 47.5 mL of water, followed by the addition of 18.8 mg of dopamine hydrochloride. The reaction suspension was then stirred at 30°C and 220 rpm for 4 h. The mixture was centrifuged, washed with water and ethanol three times, and dried at 60°C, labeled as PDA-CdS-4h NRs.
[0057] 127.5 mg of CdS NRs synthesized in Example 1 were dispersed in 50 mL of Tris-HCl aqueous solution (1 M, 2.5 mL, pH = 8.8) and 47.5 mL of water, followed by the addition of 18.8 mg of dopamine hydrochloride. The reaction suspension was then stirred at 30°C and 220 rpm for 8 h. The mixture was centrifuged, washed with water and ethanol three times, and dried at 60°C, and labeled as PDA-CdS-8h NRs.
[0058] Example 4
[0059] Single atom Mn / polydopamine / cadmium sulfide composites (Mn SAC Preparation of PDA-CdS NRs:
[0060] Mn was synthesized by photodeposition SAC / PDA-CdS NRs. 50 mg of PDA-CdS NRs and 17.51 mg of manganese acetate tetrahydrate were placed in a photoreactor, and then 30 mL of water was added and ultrasonically mixed. Then, at room temperature, 300 W xenon lamp (λ>420 nm) was used to irradiate at 400 rpm for 20 min. The sample was collected, centrifuged, washed with water and ethanol three times, and dried at 60 ° C in vacuum to obtain a single-atom Mn / polydopamine / cadmium sulfide composite material. The single-atom Mn loading was determined by ICP to be 0.01 wt%, recorded as 0.01 wt% Mn SAC / PDA-CdS NRs.
[0061] Modify the mass of manganese acetate tetrahydrate, when the mass of manganese acetate tetrahydrate is 8.7mg, 175.1mg, 870.5mg, 1751mg, respectively, it corresponds to 0.005wt%Mn SAC / PDA-CdS NRs, 0.1wt%Mn SAC / PDA-CdS NRs, 0.5wt%Mn SAC / PDA-CdS NRs, 1wt%Mn SAC / PDA-CdS NRs.
[0062] The 0.01wt% Mn SAC / PDA-CdS NRs-2h were characterized. Figure 1 For scanning electron microscopy images, Figure 2 Transmission electron microscopy images. Figure 3 This is the contact angle test diagram. Figure 4 For infrared spectrum.
[0063] Through scanning electron microscopy and transmission electron microscopy, the nanomaterial was successfully prepared, 0.01wt% Mn SAC / PDA-CdSNRs-2h is a regular nanorod structure with a length of 2 to 3 μm and a width of about 50 nm. Figure 3 The hydrophobic angle is 0°, indicating that the material is a superhydrophilic material, which is conducive to adsorbing water, promoting water to provide protons, and promoting the generation of hydrogen peroxide. Figure 4 In the infrared image, the existence of -NH, C-OH and CO structures was successfully seen, indicating the successful synthesis of the material.
[0064] Example 5
[0065] Single atom Ni / polydopamine / cadmium sulfide composite (Ni SAC Preparation of PDA-CdS NRs:
[0066] Ni was synthesized by photodeposition SAC / PDA-CdS NRs. 50mg PDA-CdS NRs and 17.51mg nickel acetate tetrahydrate were placed in a photoreactor, and then 30mL of water was added and ultrasonically mixed. Then, at room temperature, 300W xenon lamp (λ>420nm) was irradiated at 400rpm for 20min. The samples were collected, centrifuged, washed with water and ethanol three times, and dried at 60°C in vacuum to obtain a single-atom Ni / polydopamine / cadmium sulfide composite material. The single-atom Ni loading was determined by ICP to be 0.01wt%, recorded as 0.01wt% Ni SAC / PDA-CdS NRs.
[0067] Example 6
[0068] Single atom Co / polydopamine / cadmium sulfide composite (Co SAC Preparation of PDA-CdS NRs:
[0069] Co was synthesized by photodeposition. SAC / PDA-CdS NRs. 50mg PDA-CdS NRs and 17.51mg cobalt sulfate heptahydrate were placed in a photoreactor, and then 30mL of water was added and ultrasonically mixed. Then, at room temperature, 300W xenon lamp (λ>420nm) was irradiated at 400rpm for 20min. The samples were collected, centrifuged, washed with water and ethanol three times, and dried at 60°C in vacuum to obtain a single-atom Co / polydopamine / cadmium sulfide composite material. The single-atom Co loading was determined by ICP to be 0.01wt%, recorded as 0.01wt%Co SAC / PDA-CdS NRs.
[0070] Example 7
[0071] Single atom Fe / polydopamine / cadmium sulfide composites (Fe SAC Preparation of PDA-CdS NRs:
[0072] Fe was synthesized by photodeposition. SAC / PDA-CdS NRs. 50mg PDA-CdS NRs and 17.51mg ferric nitrate nonahydrate were placed in a photoreactor, and then 30mL of water was added and ultrasonicated to make them evenly mixed. Then, at room temperature, irradiate with a 300W xenon lamp (λ>420nm) at 400rpm for 20min. The samples were collected, centrifuged, washed with water and ethanol three times, and dried at 60°C in vacuum to obtain a single-atom Fe / polydopamine / cadmium sulfide composite material. The single-atom Fe loading was 0.01wt% determined by ICP, recorded as 0.01wt% Fe SAC / PDA-CdS NRs.
[0073] Experimental Example 1
[0074] In a 100 mL quartz photoreaction container, 20 mL of water, 20 mg of 0.01 wt% Mn SAC / PDA-CdS-2h NRs catalyst (cadmium sulfide morphology is rod-shaped), add magnetrons, seal, fill with oxygen, LED blue light (455nm) as the light source, the light source power is 90W, stir and react at 25℃ for 1h. After the reaction, the yield of hydrogen peroxide analyzed by iodine titration is 5615μmol·L -1 ·h -1 .
[0075] Experimental Example 2
[0076] In a 100 mL quartz photoreaction container, 20 mL of water, 20 mg of 0.01 wt% Co SAC / PDA-CdS-2h NRs catalyst (cadmium sulfide morphology is rod-shaped), add magnetrons, seal, fill with oxygen, LED blue light (455nm) as the light source, the light source power is 90W, stir and react at 25℃ for 1h. After the reaction, the yield of hydrogen peroxide analyzed by iodine titration is 5100μmol·L -1 ·h -1 .
[0077] Experimental Example 3
[0078] In a 100 mL quartz photoreaction container, 20 mL of water, 20 mg of 0.01 wt% Fe SAC / PDA-CdS-2h NRs catalyst (cadmium sulfide morphology is rod-shaped), add magnetrons, seal, fill with oxygen, LED blue light (455nm) as the light source, the light source power is 90W, stir and react at 25℃ for 1h. After the reaction, the yield of hydrogen peroxide analyzed by iodine titration is 5124μmol·L -1 ·h -1 .
[0079] Experimental Example 4
[0080] In a 100 mL quartz photoreaction container, 20 mL of water and 20 mg of 0.01 wt% Ni SAC / PDA-CdS-2h NRs catalyst (cadmium sulfide morphology is rod-shaped), add magnetrons, seal, fill with oxygen, LED blue light (455nm) as the light source, the light source power is 90W, stir and react at 25℃ for 1h. After the reaction, the yield of hydrogen peroxide analyzed by iodine titration is 5365μmol·L -1 ·h -1 .
[0081] Experimental Example 5
[0082] In a 100 mL quartz photoreaction container, 20 mL of water, 5 mg of 0.01 wt% Mn SAC / PDA-CdS-2h NRs catalyst (cadmium sulfide morphology is rod-shaped), add magnetrons, seal, fill with oxygen, LED blue light (455nm) as the light source, the light source power is 90W, stir and react at 25℃ for 1h. After the reaction, the yield of hydrogen peroxide analyzed by iodine titration is 1432μmol·L -1 ·h -1 .
[0083] Experimental Example 6
[0084] In a 100 mL quartz photoreaction container, 20 mL of water, 10 mg of 0.01 wt% Mn SAC / PDA-CdS-2h NRs catalyst (cadmium sulfide morphology is rod-shaped), add magnetrons, seal, fill with oxygen, LED blue light (455nm) as the light source, the light source power is 90W, stir and react at 25℃ for 1h. After the reaction, the yield of hydrogen peroxide detected by iodine titration is 2822μmol·L -1 ·h -1 .
[0085] Experimental Example 7
[0086] In a 100 mL quartz photoreaction container, 20 mL of water, 15 mg of 0.01 wt% Mn SAC / PDA-CdS-2h NRs catalyst (cadmium sulfide morphology is rod-shaped), add magnetrons, seal, fill with oxygen, LED blue light (455nm) as the light source, the light source power is 90W, stir and react at 25℃ for 1h. After the reaction, the yield of hydrogen peroxide analyzed by iodine titration is 4255μmol·L -1 ·h -1 .
[0087] Experimental Example 8
[0088] In a 100 mL quartz photoreaction container, 20 mL of water, 30 mg of 0.01 wt% Mn SAC / PDA-CdS-2h NRs catalyst (cadmium sulfide morphology is rod-shaped), add magnetrons, seal, fill with oxygen, LED blue light (455nm) as the light source, the light source power is 90W, stir and react at 25℃ for 1h. After the reaction, the yield of hydrogen peroxide analyzed by iodine titration is 8432μmol·L -1 ·h -1 .
[0089] Experimental Example 9
[0090] In a 100 mL quartz photoreaction container, 20 mL of water, 40 mg of 0.01 wt% Mn SAC / PDA-CdS-2h NRs catalyst (cadmium sulfide morphology is rod-shaped), add magnetrons, seal, fill with oxygen, LED blue light (455nm) as the light source, the light source power is 90W, stir and react at 25℃ for 1h. After the reaction, the yield of hydrogen peroxide analyzed by iodine titration is 11071μmol·L -1 ·h -1 .
[0091] Experimental Example 10
[0092] In a 100 mL quartz photoreaction container, 20 mL of water, 50 mg of 0.01 wt% Mn SAC / PDA-CdS-2h NRs catalyst (cadmium sulfide morphology is rod-shaped), add magnetrons, seal, fill with oxygen, LED blue light (455nm) as the light source, the light source power is 90W, stir and react at 25℃ for 1h. After the reaction, the yield of hydrogen peroxide analyzed by iodine titration is 14502μmol·L -1 ·h -1 .
[0093] Experimental Example 11
[0094] In a 100 mL quartz photoreaction container, 20 mL of water, 5 mg of 0.005 wt% Mn SAC / PDA-CdS-2h NRs catalyst (cadmium sulfide morphology is rod-shaped), add magnetrons, seal, fill with oxygen, LED blue light (455nm) as the light source, the light source power is 90W, stir and react at 25℃ for 1h. After the reaction, the yield of hydrogen peroxide analyzed by iodine titration is 3003μmol·L -1 ·h -1 .
[0095] Experimental Example 12
[0096] In a 100 mL quartz photoreaction container, 20 mL of water, 20 mg of 0.1 wt% Mn SAC / PDA-CdS-2h NRs catalyst (cadmium sulfide morphology is rod-shaped), add magnetrons, seal, fill with oxygen, LED blue light (455nm) as the light source, the light source power is 90W, stir and react at 25℃ for 1h. After the reaction, the yield of hydrogen peroxide analyzed by iodine titration is 4552μmol·L -1 ·h -1 .
[0097] Experimental Example 13
[0098] In a 100 mL quartz photoreaction container, 20 mL of water, 20 mg of 0.5 wt% Mn SAC / PDA-CdS-2h NRs catalyst (cadmium sulfide morphology is rod-shaped), add magnetrons, seal, fill with oxygen, LED blue light (455nm) as the light source, the light source power is 90W, stir and react at 25℃ for 1h. After the reaction, the yield of hydrogen peroxide analyzed by iodine titration is 3011μmol·L -1 ·h -1 .
[0099] Experimental Example 14
[0100] In a 100 mL quartz photoreaction container, 20 mL of water, 20 mg of 1 wt% Mn SAC / PDA-CdS-2hNRs catalyst (cadmium sulfide morphology is rod-shaped), add magnetrons, seal, fill with oxygen, LED blue light (455nm) as the light source, the light source power is 90W, stir and react at 25℃ for 1h. After the reaction, the yield of hydrogen peroxide analyzed by iodine titration is 2466μmol·L -1· h -1 .
[0101] Experimental Example 15
[0102] In a 100 mL quartz photoreaction container, 20 mL of water, 20 mg of 0.01 wt% Mn SAC / PDA-CdS-2h NRs catalyst (cadmium sulfide morphology is rod-shaped), add magnetrons, seal, fill with oxygen, use xenon lamp (455nm) as light source, light source power is 90W, stir and react at 25℃ for 1h. After the reaction, the yield of hydrogen peroxide analyzed by iodine titration is 4532μmol·L -1 ·h -1 .
[0103] Experimental Example 16
[0104] In a 100 mL quartz photoreaction container, 20 mL of water, 20 mg of 0.01 wt% Mn SAC / PDA-CdS-2h NRs catalyst (cadmium sulfide morphology is rod-shaped), add magnetron, seal, fill with oxygen, xenon lamp (300nm) as light source, light source power is 90W, stir and react at 25℃ for 1h. After the reaction, the yield of hydrogen peroxide analyzed by iodine titration is 3664μmol·L -1 ·h -1 .
[0105] Experimental Example 17
[0106] In a 100 mL quartz photoreaction container, 20 mL of water, 20 mg of 0.01 wt% Mn SAC / PDA-CdS-2h NRs catalyst (cadmium sulfide morphology is rod-shaped), add magnetrons, seal, fill with oxygen, use xenon lamp (600nm) as light source, light source power is 90W, stir and react at 25℃ for 1h. After the reaction, the yield of hydrogen peroxide analyzed by iodine titration is 4221μmol·L -1 ·h -1 .
[0107] Experimental Example 18
[0108] In a 100 mL quartz photoreaction container, 20 mL of water, 20 mg of 0.01 wt% Mn SAC / PDA-CdS-2h NRs catalyst (cadmium sulfide morphology is rod-shaped), add magnetrons, seal, fill with oxygen, LED blue light (300nm) as the light source, the light source power is 90W, stir and react at 25℃ for 1h. After the reaction, the yield of hydrogen peroxide analyzed by iodine titration is 3544μmol·L -1 ·h -1 .
[0109] Experimental Example 19
[0110] In a 100 mL quartz photoreaction container, 20 mL of water, 20 mg of 0.01 wt% Mn SAC / PDA-CdS-2h NRs catalyst (cadmium sulfide morphology is rod-shaped), add magnetrons, seal, fill with oxygen, LED blue light (600nm) as the light source, the light source power is 90W, stir and react at 25℃ for 1h. After the reaction, the yield of hydrogen peroxide analyzed by iodine titration is 2788μmol·L -1 ·h -1 .
[0111] Experimental Example 20
[0112] In a 100 mL quartz photoreaction container, 20 mL of water, 20 mg of 0.01 wt% Mn SAC / PDA-CdS-2h NRs catalyst (cadmium sulfide morphology is rod-shaped), add magnetrons, seal, fill with oxygen, LED blue light (455nm) as the light source, the light source power is 60W, stir and react at 25℃ for 1h. After the reaction, the yield of hydrogen peroxide analyzed by iodine titration is 2971μmol·L -1 ·h -1 .
[0113] Experimental Example 21
[0114] In a 100 mL quartz photoreaction container, 20 mL of water, 20 mg of 0.01 wt% Mn SAC / PDA-CdS-2h NRs catalyst (cadmium sulfide morphology is rod-shaped), add magnetrons, seal, fill with oxygen, LED blue light (455nm) as the light source, the light source power is 30W, stir and react at 25℃ for 1h. After the reaction, the yield of hydrogen peroxide analyzed by iodine titration is 1521μmol·L -1 ·h -1 .
[0115] Experimental Example 22
[0116] In a 100 mL quartz photoreaction container, 20 mL of water, 20 mg of 0.01 wt% Mn SAC / PDA-CdS-2h NRs catalyst (cadmium sulfide morphology is rod-shaped), add magnetrons, seal, fill with oxygen, LED blue light (455nm) as the light source, the light source power is 90W, stir and react at 30℃ for 1h. After the reaction, the yield of hydrogen peroxide analyzed by iodine titration is 6221μmol·L -1 ·h -1 .
[0117] Experimental Example 23
[0118] In a 100 mL quartz photoreaction container, 20 mL of water, 20 mg of 0.01 wt% Mn SAC / PDA-CdS-2h NRs catalyst (cadmium sulfide morphology is rod-shaped), add magnetrons, seal, fill with oxygen, LED blue light (455nm) as the light source, the light source power is 90W, stir and react at 60℃ for 1h. After the reaction, the yield of hydrogen peroxide analyzed by iodine titration is 4212μmol·L -1 ·h -1 .
[0119] Experimental Example 24
[0120] In a 100 mL quartz photoreaction container, 20 mL of water, 20 mg of 0.01 wt% Mn SAC / PDA-CdS-2h NRs catalyst (cadmium sulfide morphology is rod-shaped), add magnetrons, seal, fill with oxygen, LED blue light (455nm) as the light source, the light source power is 90W, stir and react at 90℃ for 1h. After the reaction, the yield of hydrogen peroxide analyzed by iodine titration is 1301μmol·L -1 ·h -1 .
[0121] Experimental Example 25
[0122] In a 100 mL quartz photoreaction container, 20 mL of water, 20 mg of 0.01 wt% Mn SAC / PDA-CdS-4h NRs catalyst (cadmium sulfide morphology is rod-shaped), add magnetrons, seal, fill with oxygen, LED blue light (455nm) as the light source, the light source power is 90W, stir and react at 25℃ for 1h. After the reaction, the yield of hydrogen peroxide analyzed by iodine titration is 6689μmol·L -1 ·h -1 .
[0123] Experimental Example 26
[0124] In a 100 mL quartz photoreaction container, 20 mL of water, 20 mg of 0.01 wt% Mn SAC / PDA-CdS-6h NRs catalyst (cadmium sulfide morphology is rod-shaped), add magnetrons, seal, fill with oxygen, LED blue light (455nm) as the light source, the light source power is 90W, stir and react at 25℃ for 1h. After the reaction, the yield of hydrogen peroxide analyzed by iodine titration is 8011μmol·L -1 ·h -1 .
[0125] Experimental Example 27
[0126] In a 100 mL quartz photoreaction container, 20 mL of water, 20 mg of 0.01 wt% Mn SAC / PDA-CdS-8h NRs catalyst (cadmium sulfide morphology is rod-shaped), add magnetrons, seal, fill with oxygen, LED blue light (455nm) as the light source, the light source power is 90W, stir and react at 25℃ for 1h. After the reaction, the yield of hydrogen peroxide analyzed by iodine titration is 3201μmol·L -1 ·h -1 .
[0127] Experimental Example 28
[0128] In a 100 mL quartz photoreaction container, 20 mL of water, 20 mg of 0.01 wt% Mn SAC / PDA-CdS-2h NRs catalyst (cadmium sulfide morphology is spherical), add magnetrons, seal, fill with oxygen, LED blue light (455nm) as the light source, the light source power is 90W, stir and react at 25℃ for 1h. After the reaction, the yield of hydrogen peroxide analyzed by iodine titration is 1105μmol·L -1 ·h -1 .
[0129] In summary, by changing the type of metal single atoms in Experimental Examples 1 to 4, it was found that the catalytic performance of the single-atom Mn / polydopamine / cadmium sulfide composite material was the best. This is because the manganese single atom can enrich holes, oxidize water into protons, and promote oxygen reduction to produce hydrogen peroxide.
[0130] In Experimental Examples 1 and 5 to 10, the amount of catalyst used in the catalytic reaction was changed, and it was found that the yield of hydrogen peroxide was dependent on the amount of catalyst used. In the range of 5 mg to 50 mg, the more the amount of catalyst used, the higher the yield of hydrogen peroxide. This is because there are active sites on the surface of the catalyst. Within a suitable range, the more catalysts there are, the more reactive active sites are provided, the more oxygen is adsorbed, and the more oxygen is converted into hydrogen peroxide.
[0131] In Experimental Examples 1 and 11 to 14, the loading amount of single-atom Mn was changed, and it was found that the performance was optimal when the loading amount of single-atom Mn was 0.01wt%. This is because oxygen is adsorbed on the manganese site, and as the loading amount of single-atom Mn increases, the reaction performance increases accordingly. When the loading amount is further increased, the metal single atoms will aggregate, resulting in fewer reactive sites and lower reaction activity.
[0132] In Experimental Examples 1 and 15 to 21, the wavelength and power of the light source were changed, and it was found that the catalytic performance was optimal when the LED blue light (455nm) was used as the light source and the light source power was 90 W. This is because when the light intensity is higher, the number of incident photons received per unit volume is more, the more active species are generated on the catalyst surface, the oxygen reduction reaction is faster, and more hydrogen peroxide is generated.
[0133] In Experimental Examples 1 and Experimental Examples 22 to 24, the temperature of the catalytic reaction was changed, and it was found that the reaction efficiency was highest at 30° C., and slightly lower at room temperature (25° C.). Therefore, it is shown that the present invention uses the metal single atom / polydopamine / cadmium sulfide composite material as a multiphase photocatalyst, the reaction conditions are mild, and a very high hydrogen peroxide yield can be obtained at room temperature.
[0134] In Experimental Examples 1 and 25 to 27, the polymerization time of dopamine was changed, and it was found that the polymerization time of dopamine affects the catalytic efficiency. When the polymerization time is within 2 to 6 hours, the catalytic efficiency increases with the extension of the polymerization time, but when the polymerization time is 8 hours, the catalytic efficiency decreases instead. This is because, as the polymerization time of polydopamine increases, the polydopamine shell becomes thicker and thicker, and the thicker polydopamine shell can provide more protons to the manganese at the reaction active site, promote the acquisition of protons by oxygen, and promote the generation of hydrogen peroxide. When the polymerization time of polydopamine is further extended, the thickness of the polydopamine shell is thicker, making it more difficult to load manganese. At the same time, it is more difficult for photogenerated electrons to transfer from cadmium sulfide to the manganese site through polydopamine, which is not conducive to the generation of hydrogen peroxide.
[0135] In Experimental Examples 1 and 28, the morphology of cadmium sulfide nanoparticles was changed, and it was found that cadmium sulfide nanorods had a better catalytic effect. This is because the cadmium sulfide nanorods have their own internal electric field, which leads to a better separation of electrons and holes than cadmium sulfide nanospheres, which is more conducive to the electron reduction of oxygen to generate hydrogen peroxide.
[0136] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A metal single atom / polydopamine / cadmium sulfide composite material, characterized in that: It is based on polydopamine-wrapped cadmium sulfide nanoparticles loaded with metal single atoms.
2. The metal single atom / polydopamine / cadmium sulfide composite material according to claim 1, characterized in that: The metal single atom is selected from the group consisting of single atom Cu, single atom Co, single atom Zn, single atom Fe, single atom Ni, single atom Nb, single atom In, single atom Pr, single atom La, single atom Eu, single atom V, single atom Mo, single atom Mn, single atom Cr, single atom W, single atom Zr, single atom Si, single atom Al, single atom Mg, single atom Re, single atom Ru, single atom Re, single atom Au, single atom Pt, single atom Pd and single atom Ir, preferably single atom Co, single atom Fe, single atom Ni and single atom Mn, more preferably single atom Mn; Or, in the metal single atom / polydopamine / cadmium sulfide composite material, the metal single atom loading is 0.005wt% to 1wt%, preferably 0.01wt% to 0.2wt%; Alternatively, the cadmium sulfide nanoparticles are cadmium sulfide nanorods or cadmium sulfide nanospheres; preferably, the cadmium sulfide nanorods are about 2 to 3 μm long and about 50 nm wide; and the cadmium sulfide nanospheres are about 250 to 300 nm.
3. The method for preparing the metal single atom / polydopamine / cadmium sulfide composite material according to claim 1 or 2, characterized in that: The following steps are involved: (1) dispersing cadmium sulfide nanoparticles in an alkaline buffer solution, adding dopamine hydrochloride, and reacting to obtain polydopamine-coated cadmium sulfide nanoparticles; (2) Mixing a metal single atom source with polydopamine-wrapped cadmium sulfide nanoparticles to obtain a mixture; the mixture undergoes a photodeposition reaction to obtain the metal single atom / polydopamine / cadmium sulfide composite material.
4. The preparation method according to claim 3, characterized in that: In step (1), the mass ratio of cadmium sulfide nanoparticles to dopamine hydrochloride is (12-14):(1.5-2), preferably 12.75:1.88; Alternatively, dopamine hydrochloride is added and stirred to react to obtain polydopamine-wrapped cadmium sulfide nanoparticles, the stirring rate is 200 to 300 rpm, preferably 220 rpm; the stirring time is 2 to 8 hours.
5. The preparation method according to claim 3, characterized in that: In step (2), the metal single atom source includes CuCl2, ZnCl2, Fe(NO3)3, C 10 H5B 20 , InCl3, PrCl3, Cl3La, C6H9EuO6, Cl3V, C8H 12 Mo2O8, C6H9O6Cr, WCl6, C8H 12 O8Zr、C8H 12 One of O8Si, AlCl3, MgCl2, Cl5Re, C6H9O6Ru, HAuCl4, HPtCl4, PdCl2, Cl4Ir, Mn(CH3COO)2, Ni(CH3COO)2, CoSO4 and Fe(NO3)3.
6. The preparation method according to claim 3, characterized in that: In step (2), a metal single atom source is mixed with cadmium sulfide nanoparticles wrapped with polydopamine to obtain a mixture; and the mixture undergoes a photodeposition reaction to obtain the metal single atom / polydopamine / cadmium sulfide composite material. The method comprises: The method comprises dispersing a metal single atom source and cadmium sulfide nanoparticles wrapped by polydopamine in water, mixing them evenly, and then irradiating the mixed solution with a 200-400W xenon lamp for 15-30 minutes under a vacuum state to obtain the metal single atom / polydopamine / cadmium sulfide composite material; Preferably, the mixed solution is irradiated with light for 20 minutes using a 300W xenon lamp in a vacuum state.
7. Use of the metal single atom / polydopamine / cadmium sulfide composite material according to claim 1 or 2 and / or the metal single atom / polydopamine / cadmium sulfide composite material prepared by the preparation method according to any one of claims 3 to 6 as a photocatalyst.
8. The use according to claim 7, characterized in that The applications include the photocatalytic synthesis of hydrogen peroxide from oxygen and water.
9. A method for synthesizing hydrogen peroxide, characterized in that: include: The metal single atom / polydopamine / cadmium sulfide composite material according to claim 1 or 2 and / or the metal single atom / polydopamine / cadmium sulfide composite material prepared by the preparation method according to any one of claims 3 to 6 is added into water, oxygen is introduced and the mixture is reacted under a light source to obtain hydrogen peroxide.
10. The synthesis method according to claim 9, characterized in that The power of the light source is 30-90w, and the wavelength of the light source is 300-600nm; Alternatively, the reaction temperature under light source is 25 to 90°C.